Pay attention to treating a subgroup of positional obstructive sleep apnea patients - Yu-Ting Chou; Tsung-Ming Yang; Chin-Kuo Lin; Shu-Yi Huang; Ying-Huang Tsai; Ju-Fang Chang; Yu-Jung Hou; Yu-Ching Lin (Journal of the Formosan Medical Association, 2017)
Positional obstructive sleep apnea (OSA) is defined as an apnea hypopnea index at least twice as high in the supine position as in the lateral position. Whether a positional OSA patient persistently has positional OSA in the follow-up period is unknown. This study was conducted to investigate the maintenance of the positional effect on OSA patients and the predictors of changing from positional OSA to nonpositional OSA. Methods: Patients who were diagnosed to have positional OSA were screened for a follow-up polysomnography (PSG), which evaluated the effect of the same lateral position as baseline PSG on the severity of OSA. Those who met the criteria of positional OSA in both PSGs were classified as the unchanged group, the others were classified as the changed group. Results: Seventy-eight positional OSA patients were enrolled in the final analyses. Twenty-seven of the enrolled patients (35%) were changed to nonpositional OSA patients in the second PSG. A higher apnea index in the lateral position was found in the changed group compared with that in the unchanged group (p = 0.02). Logistic regression also showed that the apnea index in the lateral position was the only independent predictor of changing from positional OSA to nonpositional OSA in the follow-up PSG (odds ratio = 1.13, p = 0.004). Conclusion: One-third of positional OSA patients who had a high apnea index in the lateral position tends to become nonpositional OSA patients in the follow-up PSG and must be closely monitored if receiving positional therapy only.